(* plus *)
theorem monotonic_le_plus_r:
\forall n:nat.monotonic nat le (\lambda m.n + m).
-simplify.intros.elim n.
-simplify.assumption.
-simplify.apply le_S_S.assumption.
+simplify.intros.elim n
+ [simplify.assumption.
+ |simplify.apply le_S_S.assumption
+ ]
qed.
theorem le_plus_r: \forall p,n,m:nat. n \le m \to p + n \le p + m
theorem le_plus: \forall n1,n2,m1,m2:nat. n1 \le n2 \to m1 \le m2
\to n1 + m1 \le n2 + m2.
intros.
+(**
+auto.
+*)
+apply (transitive_le (plus n1 m1) (plus n1 m2) (plus n2 m2) ? ?);
+ [apply (monotonic_le_plus_r n1 m1 m2 ?).
+ apply (H1).
+ |apply (monotonic_le_plus_l m2 n1 n2 ?).
+ apply (H).
+ ]
+(* end auto($Revision$) proof: TIME=0.61 SIZE=100 DEPTH=100 *)
+(*
apply (trans_le ? (n2 + m1)).
apply le_plus_l.assumption.
apply le_plus_r.assumption.
+*)
qed.
theorem le_plus_n :\forall n,m:nat. m \le n + m.
intro.reflexivity.
qed.
+(* times and plus *)
+theorem lt_times_plus_times: \forall a,b,n,m:nat.
+a < n \to b < m \to a*m + b < n*m.
+intros 3.
+apply (nat_case n)
+ [intros.apply False_ind.apply (not_le_Sn_O ? H)
+ |intros.simplify.
+ rewrite < sym_plus.
+ unfold.
+ change with (S b+a*m1 \leq m1+m*m1).
+ apply le_plus
+ [assumption
+ |apply le_times
+ [apply le_S_S_to_le.assumption
+ |apply le_n
+ ]
+ ]
+ ]
+qed.
+
(* div *)
theorem eq_mod_O_to_lt_O_div: \forall n,m:nat. O < m \to O < n\to n \mod m = O \to O < n / m.
]
qed.
+theorem divides_div: \forall d,n. divides d n \to divides (n/d) n.
+intros.
+apply (witness ? ? d).
+apply sym_eq.
+apply divides_to_div.
+assumption.
+qed.
+
theorem div_div: \forall n,d:nat. O < n \to divides d n \to
n/(n/d) = d.
intros.
[apply (nat_case m)
[intro.apply divides_n_n
|simplify.intros.apply False_ind.
- apply not_eq_true_false.apply sym_eq.assumption
+ apply not_eq_true_false.apply sym_eq.
+ assumption
]
|intros.
apply divides_b_true_to_divides1
absurd (n \divides m).assumption.assumption.
qed.
+theorem divides_to_divides_b_true1 : \forall n,m:nat.
+O < m \to n \divides m \to divides_b n m = true.
+intro.
+elim (le_to_or_lt_eq O n (le_O_n n))
+ [apply divides_to_divides_b_true
+ [assumption|assumption]
+ |apply False_ind.
+ rewrite < H in H2.
+ elim H2.
+ simplify in H3.
+ apply (not_le_Sn_O O).
+ rewrite > H3 in H1.
+ assumption
+ ]
+qed.
+
theorem not_divides_to_divides_b_false: \forall n,m:nat. O < n \to
\lnot(n \divides m) \to (divides_b n m) = false.
intros.
reflexivity.
qed.
+theorem divides_b_div_true:
+\forall d,n. O < n \to
+ divides_b d n = true \to divides_b (n/d) n = true.
+intros.
+apply divides_to_divides_b_true1
+ [assumption
+ |apply divides_div.
+ apply divides_b_true_to_divides.
+ assumption
+ ]
+qed.
+
theorem divides_b_true_to_lt_O: \forall n,m. O < n \to divides_b m n = true \to O < m.
intros.
elim (le_to_or_lt_eq ? ? (le_O_n m))
definition totient : nat \to nat \def
\lambda n.sigma_p n (\lambda m. eqb (gcd m n) (S O)) (\lambda m.S O).
-
+lemma totient1: totient (S(S(S(S(S(S O)))))) = ?.
+[|simplify.
+
theorem totient_times: \forall n,m:nat. (gcd m n) = (S O) \to
totient (n*m) = (totient n)*(totient m).
intros.